0561 Differences in Nasopharyngoscopic Airway Form Between Awake and Sleep, Sitting and Recumbent Position and Techniques. (27th May 2020) - Nishimura, Y; Hamed, M
Abstract: Introduction: To examine and compare the information derived from flexible fiber-optic nasopharyngoscopy in awake mimic snoring (AMS), Müller's Maneuver (MM) and drug-induced sleep endoscopy (DISE), to determine if AMS and MM can be used in substitution for DISE as a streamlined method. We investigated their relation with the level and pattern of obstruction detected on AMS, MM and DISE. Methods: This is a retrospective study of 15 obstructive sleep apnea patients with apnea hypopnea index from 8.3 to 105.2, ages 20 to 80 were included. Each patient underwent polysomnography and thorough a physical examination, including flexible nasopharyngoscopy with AMS, MM and DISE. Airway obstruction on these endoscopic procedures were described according to airway level and pattern of obstruction. They were classified 5 different types; Uvula type: anterior-posterior vibration of the uvula, no airway obstruction; L-R velum type: lateral (the left and right directions) airway narrowing at velum level, no airway obstruction; A-P velum type: anterior-posterior total airway obstruction at velum level; Tonsillar type: total airway obstruction at pharyngeal level; Circumferential type: circumferential total airway obstruction at velum level. AMS and MM were performed with patients in sitting and in recumbent position. DISE was performed only in recumbent position. Results: In review of the three procedures, the results were much different. Airway was obstructed in all cases(100%, 15 of 15)in DISE, but not all cases in AMS and MM. When tonsillar type was seen in AMS, it was also seen in MM and DISE(100%, 5 of 5). Conclusion: Flexible fiber-optic nasopharyngoscopy appears to be useful for evaluating airway obstruction. It might be not suitable to use AMS and MM in substitution for DISE(except tonsillar type). Muscle tonic relaxation of the upper airway between AMS, MM and DISE might be different (DISE>MM>AMS, recumbent>sitting). Support: